Efektivitas Komik Digital sebagai Media Pembelajaran Daring pada Materi Sistem Persamaan Linear Dua Variabel - Davi Maya Maghrobi Arum; Wahyuni Suryaningtyas; Sandha Soemantri (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhhammadiyah kendari, 2022)
The purpose of this study are to describe the teacher's implementation of managing learning, student activities during learning, student learning outcomes, student responses after participating in learning using Digital Comics as an online learning medium on SPLDV material. The method used is quantitative descriptive research with a One-Shot Case Study design. Subject the research consisted of 31 students of SMP Muhammadiyah 13 Surabaya. The results show that (1) the effectiveness of teachers in managing to learn is in the very good category with an average of 95%, (2) the effectiveness of student activities during learning is included in the very active category with an average of 3.70, (3) the effectiveness of completeness results student learning is said to be complete with a classical completeness percentage of 97%, (4) the effectiveness of student responses is included in the very positive category. From the result above, it can be concluded that the use of Digital Comics as an online learning media is effective for students learning mathematics outcomes in SPLDV subjects at SMP Muhammadiyah 13 Surabaya.